2015
DOI: 10.1111/jdv.13515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical patterns and associated factors in patients with hand eczema of primarily occupational origin

Abstract: Environmental and individual factors are associated with different clinical patterns of HE in patients taking part in the TIP. They may influence the prognosis and should be considered in the individual management of disease. Tobacco smoking may be in particular a risk factor for vesicular HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
5
20
1
1
Order By: Relevance
“…Finally, atopic dermatitis is a well‐known risk factor for more severe and chronic hand eczema . The number of patients with atopic hand eczema in this study was in line with previous studies (21.5%‐57.5%) …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, atopic dermatitis is a well‐known risk factor for more severe and chronic hand eczema . The number of patients with atopic hand eczema in this study was in line with previous studies (21.5%‐57.5%) …”
Section: Discussionsupporting
confidence: 91%
“…34 The number of patients with atopic hand eczema in this study was in line with previous studies (21.5%-57.5%). 32,33 A limitation of our study is the monocentric design in a tertiary referral center. Presumably this patient cohort included more patients with a difficult-to-treat hand eczema in all groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to lifestyle factors, recent reports have indicated associations between hand eczema and tobacco smoking, physical activity, and high BMI , although there is no agreement on this , which might be attributable to the variable subdiagnoses of hand eczema included in the studies. One study found smoking to be a particular risk factor for vesicular hand eczema . In the present study, no significant difference was found between hyperkeratotic hand eczema and other subgroups of hand eczema with respect to tobacco smoking.…”
Section: Discussioncontrasting
confidence: 76%
“…It is known that there are several types of occupational HD, which overlap and are difficult to distinguish. 38 Moreover, the mild symptoms of HD (mostly only slight erythema) observed in most HCWs at entry, implying that there was limited room for improvement, constitute another factor that might have diluted the effect of the intervention with regard to severity. As our study population was a working population, HECSI scores were markedly lower than in patients in secondary prevention studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%